If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 7m + -3m + -6 Reorder the terms: 6 = -6 + 7m + -3m Combine like terms: 7m + -3m = 4m 6 = -6 + 4m Solving 6 = -6 + 4m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4m' to each side of the equation. 6 + -4m = -6 + 4m + -4m Combine like terms: 4m + -4m = 0 6 + -4m = -6 + 0 6 + -4m = -6 Add '-6' to each side of the equation. 6 + -6 + -4m = -6 + -6 Combine like terms: 6 + -6 = 0 0 + -4m = -6 + -6 -4m = -6 + -6 Combine like terms: -6 + -6 = -12 -4m = -12 Divide each side by '-4'. m = 3 Simplifying m = 3
| .15x-3=.4(-5) | | 1+r=-4(-6r-4)+8 | | 8(5x+1)=5x-6x | | c/2+1=9/2 | | -6x=-3x+12 | | 6x^2-17x=17 | | 17+(828-305-4021y)=3-40 | | (1/7)(x+21)=-6 | | f(x)=-4x^2+9x+7 | | 5x-3=7x-25 | | -0.7x+9.89=-0.9x+4.69 | | 4x-13=-6x | | 50-7x=-34 | | (3/4)x-22=9 | | -0.5x+6.47=-0.7x+2.47 | | 5/6x=2-11/12x | | 11(4X-4)+7=8X-9 | | 8x+2.3=6x+2.3 | | 13-1x= | | 6x1x2/3x7 | | 6-2x=5x-9+9 | | -11-7x=-60 | | 5x-7x-13=-2x+6-13 | | 29=-16+9x | | 7x2/3-1x6 | | 6x+4(1x-3)=48 | | 4-3(x+3)=11-7(5-2x) | | 32x^2+28xy-15y^2=0 | | 11X/5(4-7)=6X+8 | | 15+3x=x-3 | | 0.5x+6.47=-0.7x+2.47 | | -5w=2w-21 |